Training (Tadrib) Dalam Perspektif Islam - Fathoni, Wildan; Jannah, Nur; A, Ansori; Anwar, Kasful (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This paper discusses the basic concept of training (tadrib) from an Islamic perspective and its implications for Islamic educational management. This study uses a literature review method by analyzing various sources, including the Qur'an, hadith, and related literature. The results of the study show that the concept of tadrib in Islam has a broader meaning than just skill training. Tadrib in Islam aims to develop individuals holistically, both intellectually, spiritually, and socially. The implications of tadrib in Islamic educational management include improving the professionalism of educators, improving the quality of educational institution management, improving the quality of educational services, building character and noble morals, and adapting to developments in technology and educational innovation. Training and development of human resources in Islamic educational institutions is the key to achieving these goals. Thus, training from an Islamic perspective is not only relevant to improving the quality of education but also to forming a generation that is faithful, knowledgeable, and has noble character